Pengaruh Work Life Balance, Beban Kerja, Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan (Studi Pada Pt. Ciomas Adisatwa Di Kabupaten Badung) - Ni Made Fitria Rahayu; Made Yudi Darmita; Laras Oktaviani (Journal Research of Management, 2024)
This research explores how work-life balance, workload, and work environment influence job satisfaction among employees at PT. Ciomas Adisatwa, Kabupaten Badung. Utilizing a complete sample of 60 employees through saturated sampling, the study employs quantitative analysis, including multiple regression with Y = 6.023 + 0.553X1 - 0.203X2 + 0.343X3 as the developed regression model. Results indicate a positive and significant effect of work-life balance and work environment on job satisfaction. In contrast, workload negatively impacts satisfaction. These factors together explain 57.2% of job satisfaction variability, with the remaining influenced by unexamined variables. Work-life balance emerges as the most influential factor. Keywords: work-life balance, workload, work environment, job satisfaction.